Donations for Palestine: Amanah as a Moderating Variable in the Effect of Transparency and Institutional Image on Donor Trust - faturahman; Atar Satria Fikri; Ferri Saputra Tanjung; Wan Nur Fazni Wan Mohamad Nazarie (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2026)
This study focuses on analyzing the impact of transparency and institutional image on donor trust, as well as the ability of the variable amanah to moderate the effect of transparency and institutional image on donor trust in fundraising and donation management for Palestine. This research employs a quantitative approach. The population and sample consist of 100 DT Peduli Jambi donors who contributed to Palestine, selected using probability sampling with a simple random sampling technique. A Likert-scale questionnaire was used as the data collection instrument. Data analysis was conducted using multiple regression and moderated regression analysis. Based on the findings and discussion, transparency and institutional image are the main factors influencing donor trust. Both function as signals that reduce information asymmetry and shape public perceptions of institutional credibility and reputation. The inability of amanah to moderate the relationship between transparency, institutional image, and donor trust represents an important finding of this study. Amanah does not directly influence donor trust in this context but rather functions as an inherent moral foundation within the institution.